THE EFFECTIVENESS OF CLASS DIVISION BASED ON STIFIN (INTELLIGENCE MACHINE) AT THE SUKMA MEDAN COLLEGE OF MANAGEMENT SCIENCES, ESPECIALLY IN KIP STUDENTS IN THE SECOND SEMESTER OF THE AFTERNOON CLASS - Cece Harahap (Indonesian Journal of Multidisciplinary Science, 2022)
Stifin is a tool for detecting intelligence and a person's brain type, it is used to find out a person's character and to find out what learning methods are suitable for each student. This type of research is a quantitative descriptive study using a survey method conducted online. Primary data collection in this study was carried out by distributing online questionnaires to 34 respondents who were students of KIP STIM SUKMA MEDAN which included students studying in the second semester in afternoon classes with combined concentrations. Respondents from this study were students of right brain b and left brain b management study program which included 2nd semester students. In this study students who were respondents and were willing to fill out google forms. Based on the analysis above, it can be concluded that many students think that they are more familiar with character their personal after knowing their MK. but having the Constitutional Court and adjusting the class according to the Constitutional Court does not guarantee that all students are comfortable, because there is no difference in assignments or anything else between right brain class B and left brain B.